Conceptual axiomatic design on ergonomic electric scooter - Ooi, Y.M (Universiti Malaysia Sarawak, UNIMAS, 2010)
The conceptual design of Ergonomic Electric Scooter is developed based on axiomatised design parameters. Axiomatised design parameters are all of the possible area of designs, systems, components and parts that can exist in a concept design. Axiomatised design parameters are obtained based on benchmarking from existing products, designs, systems, components, and etc. in nowadays markets and technologies. After the axiomatised design parameters are obtained, market survey is needed to obtain the most preferred functional requirements by customers and users. Based on the functional requirements listed, the highest weight functional requirements will be set as the concept selection priority based on the axiomatised design parameters. Mutually exclusive design parameters will be analysed based on priority. Elimination of impossible design parameters will be carried out and the finalised design parameters will serve as the base reference when conceptual design and detailed design are carried out in the design phase. Once the detailed designs are obtained, a prototype will be fabricated in order to evaluate the design performance and functionality based on the objectives and aims of this project.